2019
DOI: 10.1063/1.5080980
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of spectrally broadband Huygens sources using low-index spheres

Abstract: Manipulating the excitation of resonant electric and magnetic multipole moments in structured dielectric media has unlocked many sophisticated electromagnetic functionalities. This invited article demonstrates the experimental realization of a broadband Huygens' source. This Huygens' source consists of a spherical particle that exhibits a well-defined forward-scattering pattern across more than an octave-spanning spectral band at GHz frequencies, where the scattering in the entire backward hemisphere is suppre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…39 The alignment of different resonances can then increase the helicity preserving bandwidth. 26,40 4 Methods…”
Section: Discussionmentioning
confidence: 99%
“…39 The alignment of different resonances can then increase the helicity preserving bandwidth. 26,40 4 Methods…”
Section: Discussionmentioning
confidence: 99%
“…40 Thus far, the Huygens source has attracted extensive attention for production of unidirectional far-field antennas. 41,42 Based on this far-field property, efficient Huygens metasurfaces with arbitrary EM wave fronts have recently been proposed for all-dielectric [43][44][45][46] and actively controlled systems. 47 Specifically, Picardi et al 48 theoretically revealed the near-field directionality of a Huygens dipole.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has already been proven successful in predicting some different effects that the two properties can have in light–matter interactions. [ 36–38 ]…”
Section: Introductionmentioning
confidence: 99%